IbM untuk Kapasitas dan Kualitas Produksi, Manajemen Keuangan dan Pemasaran Usaha Mikro Krupuk di Surabaya - Zakariya .; Kunto Inggit Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
Abstract.Â â€œSumberRejekiâ€ micro owner is Mrs Liana which located at Jl. Gunung Anyar Tambak I/63 Surabaya. This business has been established in 1986 and operates in the field of business crackers. Type crackers produced include: shellfish crackers, shrimp crackers, plain crackers and specialtaste crackers. While the Micro Business Owners â€œJaya Abadiâ€ is MsNurMuniroh located on Jl. GunungAnyarTambak I/55 Surabaya. This business has been established since 1989 and operates on the business field cracker. Type crackers produced include: shellfishcrackers, shrimp crackers, plain crackers and special taste crackers. The main problems faced through â€œSumberRejekiâ€ and â€œJaya Abadiâ€ micro business are the quantity and quality of production is not optimal yet and both couldâ€™nt make financial bookkeeping business and less distribution lobbied about market products to department stores and shops centers. By using science and technology from the Ipteks bagi Masyarakat (IbM) can be expected improving the quantity and quality of crackers production, as well as to make financial efforts and to expand marketing network.Keywords: Production, Finance and Marketing